Pemetaan minat vokasional RIASEC dan kepribadian TIPI sebagai strategi optimalisasi konsep diri mahasiswa baru program studi promosi kesehatan - Risanita Fardian Farid; Welan Mauli Angguna; Yuni Fatimatizzahro; Erick Zicof; Evi Maria Lestari Silaban (Penamas: Journal of Community Service, 2026)
New students of the Bachelor of Applied Health Promotion Program at Poltekkes Kemenkes Padang frequently encounter vocational anxiety and a negative fixed mindset regarding the compatibility of their personal characteristics with the health promoter role. This community service project aimed to optimize students' self-concept through a psychological potential mapping program based on self-assessments using the RIASEC Vocational Interest Questionnaire and the Ten-Item Personality Inventory (TIPI). The activity was carried out through a digital assessment of 130 new students and continued with an interactive psychoeducational seminar. Results showed that the social type dominated vocational interest profiles (40.0%), followed by Investigative (26.9%), indicating strong alignment with health promotion competency demands. Personality profiles revealed the highest scores in Conscientiousness and Agreeableness. Impact evaluation demonstrated a significant increase in students' understanding of the five core health promoter graduate profiles. Additionally, 99.1% of participants reported that the activity successfully strengthened their professional self-confidence. In conclusion, this integrated interest and personality mapping intervention effectively optimized students' self-concept.